A comparative study to determine intermittent versus continuous phototherapy for reducing neonatal hyperbilirubinemia at tertiary care hospital in Chennai, Tamil Nadu, India - Suri, Diksha; A. P., Krithika; Somasekar, R. (International Journal of Contemporary Pediatrics, 2019)
Background: Phototherapy is safe and effective in neonatal hyperbilirubinemia. Despite its worldwide application, questions regarding methods of optimizing efficacy remain unanswered, turning the infant is believed to be one of the methods to improve. Severe neonatal hyperbilirubinemia is associated with kernicterus, condition characterized by athetoid spasticity, gaze and visual abnormalities, and sensory-neural hearing loss. It may also be associated with mental retardation. Aim of this study was conducted to compare the efficacy of intermittent with continuous phototherapy. Methods: Study was conducted in 100 neonates from February 2018 to July 2018 in Sree Balaji medical college and hospital. Inclusion criteria were weight >2000 grams, absence of other concomitant diseases, and hyperbilirubinemia not requiring exchange transfusion. The neonates were randomly divided into two groups. Continuous phototherapy group received phototherapy on and off for 2 hours and half an hour respectively and the intermittent phototherapy group on and then off for one hour. Serum total bilirubin levels were measured in every 36 hours. Results: Mean age of the patients was 3.89±1.83(p=.91) days, mean baseline bilirubin was 17.56mg/dl±1.42 (p=0.36), while the mean follow-up bilirubin was 12.85mg/dl±1.65 (p=.95), and the mean difference between the baseline and follow-up bilirubin was 4.7 mg/dl±1.19 (p=.32). For group A and B babies, the mean difference between the baseline and follow-up bilirubin was 4.78 mg/dl±1.20 (p=.32) and 4.63mg/dl±1.18(p=0.32) respectively. The difference between the mean age, mean baseline bilirubin, mean follow-up bilirubin, and the mean decrease in bilirubin for both the groups was statistically not significant. Conclusions: Intermittent and continuous phototherapies were found to be equally effective for reducing neonatal hyperbilirubinemia.